How to consider target heart rate in patients with systolic heart failure. (27th June 2020) - Izumida, Toshihide; Imamura, Teruhiko; Nakamura, Makiko; Fukuda, Nobuyuki; Kinugawa, Koichiro
Abstract: Aims: Heart rate reduction therapy using ivabradine, a selective inhibitor of the funny current of the sinoatrial node, is widely used in the systolic heart failure cohort. However, the optimal target of heart rate remains controversial. The association between heart rate and 'overlap' between E‐wave and A‐wave in the pulse wave transmitral flow Doppler echocardiography might be a key to find the ideal heart rate in each individual. Methods and results: We performed transthoracic echocardiography in patients with systolic heart failure, and the association between heart rate, deceleration time, and overlap length between E‐wave and A‐wave was assessed. In total, 368 patients with systolic heart failure (median 76 years old, 190 men, median ejection fraction 40%) were included. The measured overlap length was 35 (−72, 115) ms. Given the results of multiple linear regression analyses, we constructed a formula: estimated overlap length (ms) = −589 + 6.2 × heart rate (bpm) + 0.81 × deceleration time (ms), which had a good agreement with actually measured one ( r = 0.62). The ideal heart rate, at which the overlap length is 'zero' and probably cardiac output is maximized, is calculated as follows: ideal heart rate (bpm) = 93 – 0.13 × deceleration time (ms). Conclusions: We proposed a novel formula using deceleration time to estimate ideal heart rate that achieves a zero overlap between E‐wave and A‐wave in patients with systolic heart failure. Prognostic impact of the formula‐guided heart rate optimization should be studied.